Marina Tsvetaeva in Yerevan Publications and Editions (1962-2017) - GONCHAR, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
The collection is composed in commemoration the 125th anniversary of XX century great Russian poet Marina Tsvetaeva. It presents numerous addresses to the name and work of M.Tsvetaeva in Armenia in the course of more than half a century.The material (publications, translations, studies, editions) is presented in the bibliography, many components of it are accompanied by annotations, commentary, fragments from texts.
Keywords: Tsvetaeva, Armenia, collection of materials, publication, article, essay, translation, edition